Effectiveness of a Social Marketing Mix Intervention on Changing the Smoking Behavior of Santri in Traditional Islamic Boarding Schools in Indonesia - Ismail Ismail; Teuku Tahlil; Nursalam Nursalam; Zurnila Marli Kesuma; Syarifah Rauzhatul Jannah; Hajjul Kamil; Fithria Fithria; Kintoko Rochadi (Korean Society for Preventive Medicine, 2022)
Objectives: This study investigated the effectiveness of the social marketing mix approach in increasing students' knowledge about smoking, promoting positive attitudes toward smoking cessation, and decreasing smoking behavior. Methods: This quantitative research study incorporated a quasi-experimental method with a pretest-posttest non-equivalent group design. Using the purposive sampling technique, 152 smoking students were selected as participants. They were divided into 2 equal groups, with 76 students in the control group and 76 in the intervention group. The data were collected using questionnaires and analyzed with the chi-square test, independent t-test, Wilcoxon signed-rank test, and Mann-Whitney U-test. Results: The social marketing mix intervention was effective in increasing the students' knowledge about smoking (p<0.001), improving their attitude toward smoking cessation (p<0.001), and reducing their smoking behavior (p=0.014). Conclusions: This approach should be implemented by local governments to reduce smoking behavior in the community, especially among teenagers, in addition to instituting a smoking ban and applying fines.